2009
DOI: 10.1016/j.cell.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PKD by the MAPK p38δ in Insulin Secretion and Glucose Homeostasis

Abstract: SummaryDysfunction and loss of insulin-producing pancreatic β cells represent hallmarks of diabetes mellitus. Here, we show that mice lacking the mitogen-activated protein kinase (MAPK) p38δ display improved glucose tolerance due to enhanced insulin secretion from pancreatic β cells. Deletion of p38δ results in pronounced activation of protein kinase D (PKD), the latter of which we have identified as a pivotal regulator of stimulated insulin exocytosis. p38δ catalyzes an inhibitory phosphorylation of PKD1, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
240
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(249 citation statements)
references
References 47 publications
8
240
1
Order By: Relevance
“…Consistent with a role for the GPCR-induced fragmentation changes in secretion observed here, Golgi fragmentation has been observed in secretory pancreatic acinar cells activated with a GPCR agonist, cholecystokinin (28). Our results are also consistent with the ablation of p38Δ enzyme in pancreatic β cells, which leads to overactivation of PKD, increased insulin secretion, and fragmentation of the entire Golgi complex (8). The receptor-induced translocation of the G protein βγ complex may thus serve as an unexpected mechanism at the basis of the regulation of secretion.…”
Section: M3-receptor-induced Increase In Insulin Secretion Is Mediatesupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with a role for the GPCR-induced fragmentation changes in secretion observed here, Golgi fragmentation has been observed in secretory pancreatic acinar cells activated with a GPCR agonist, cholecystokinin (28). Our results are also consistent with the ablation of p38Δ enzyme in pancreatic β cells, which leads to overactivation of PKD, increased insulin secretion, and fragmentation of the entire Golgi complex (8). The receptor-induced translocation of the G protein βγ complex may thus serve as an unexpected mechanism at the basis of the regulation of secretion.…”
Section: M3-receptor-induced Increase In Insulin Secretion Is Mediatesupporting
confidence: 79%
“…S1), indicating alteration of the entire Golgi structure. This exaggerated response is similar to the breakdown of the entire Golgi complex that has previously been seen when Golgi protein kinase D (PKD) was overly activated (8,9). When distribution of TGN46 and GM130 was analyzed in cells in which γ11 was not transfected, receptor activation had no effect, showing that γ11 is necessary for fragmentation.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Mice with disruption of other p38 isoforms are viable and fertile. Recently, it was reported that mice lacking p38g showed defects in insulin secretion in pancreatic β cells (Sumara et al, 2009). p38α is a serine/threonine kinase which rapidly responds to stresses such as endotoxic lipopolysaccharide (LPS) and heat shock (Han and Sun, 2007;Hui et al, 2007b). p38α phosphorylation is regulated by MKK3 and MKK6, which are activated by upstream kinases, such as MTK1 and ASK1 (Han and Sun, 2007;Hui et al, 2007b).…”
Section: P38smentioning
confidence: 99%
“…Recent reports implicate p38γ and p38δ in metabolic diseases, cancer, and tissue regeneration, raising interest in this pathway as a therapeutic target for drugs. p38δ regulates insulin secretion and survival of pancreatic β-cells, implying a pivotal role for this kinase in diabetes (12). Moreover, studies in mice suggest that p38γ blocks premature differentiation of satellite cells, a skeletal muscle stem-cell population that participates in adult muscle regeneration (13).…”
mentioning
confidence: 99%